Corruption and the Environment - Leitão, Alexandra (2017)
Corruption is a serious problem and social ethics has a significant impact on all societies. It is a phenomenon which is globally widespread and can be generally defined as the use of public power to benefit a private interest. It is a complex and multifaceted concept with several and heavy complications for the economy and environmental sustainability. Despite the existing theorizations and descriptions of the political economy concerning environment/society interactions and widespread evidence of bribery and illegal exchange in natural resources management, nowadays, fighting corruption goes on widely ineffective, with serious consequences for environmental quality. The main focus of this study is the different forms of corruption and its consequences and costs to the environment, especially in resource-rich developing countries. It explores a few practical examples taken from these countries due to the linkages between corruption and weak environmental governance. The institutional set-up of the country such as the characteristics of the political and judicial system determines the extent of corruption. In such a context, transparency has been described as a cure for corruption. Good governance including a broad commitment to the rule of law is crucial for environmental sustainability and is a way to put a stop to the devastating impact corruption has had on the environment.